2020
DOI: 10.1002/marc.202000415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Recycling of Packaging Plastics: A Review

Abstract: The current global plastics economy is highly linear, with the exceptional performance and low carbon footprint of polymeric materials at odds with dramatic increases in plastic waste. Transitioning to a circular economy that retains plastic in its highest value condition is essential to reduce environmental impacts, promoting reduction, reuse, and recycling. Mechanical recycling is an essential tool in an environmentally and economically sustainable economy of plastics, but current mechanical recycling proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
818
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 891 publications
(831 citation statements)
references
References 210 publications
(390 reference statements)
4
818
0
9
Order By: Relevance
“…This group includes polypropylene (PP), polyethylene (PE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), polyvinyl chloride (PVC), polyurethane (PU), polyethylene terephthalate (PET), and polystyrene (PS). PET, PP, PVC, PS, and PE are the five most used polymers for packaging applications (Schyns and Shaver 2020). Aside from its use as a base material, plastics can also be used as complementary material in a multi-layered or multi-material foodware (Geueke et al 2018).…”
Section: Plastics As a Foodware Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This group includes polypropylene (PP), polyethylene (PE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), polyvinyl chloride (PVC), polyurethane (PU), polyethylene terephthalate (PET), and polystyrene (PS). PET, PP, PVC, PS, and PE are the five most used polymers for packaging applications (Schyns and Shaver 2020). Aside from its use as a base material, plastics can also be used as complementary material in a multi-layered or multi-material foodware (Geueke et al 2018).…”
Section: Plastics As a Foodware Materialsmentioning
confidence: 99%
“…For example, for PET, its high elongation at break value weakens significantly by a factor of 4 after being mechanically recycled 4 to 5 times. As for PP, multiple recycling reduces its molecular weight, critical to its material performance (Schyns and Shaver 2020). Thus, to make recycled plastics usable, virgin plastics are usually added to the final product to balance its product performance.…”
Section: Recycled Plasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrusion is a mechanical process that is mainly used in plastic mechanical recycling. The degradation of recycled plastics in the extrusion process is caused by chain scission or the forming of cross-links [7,8]. From our previous work, it can be found that the degradation of plastics was not caused by chemical degradation but that the physical degradation was the main reason [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A review of these policies can be found in [32,33], which highlights the reduction in consumption, greater collection of plastic, regulation of the entire plastic value chain, and recycling. Recycling is one of the most essential actions to avoid increases in environmental pollution [34]. Recycling involves different agents throughout the whole management chain for the recycling of marine plastic waste, including collection, sorting, cleaning, volume reduction and separation [35].…”
Section: Introductionmentioning
confidence: 99%